Water Justice Amid Climate Crisis: Implementing Risk-Based Water Allocation and Strengthening Farmer Association In-stitutional Capacity - Hari Kusuma Yuda Tama; Waluyo Waluyo (Prosiding Seminar Nasional Ilmu Hukum, 2025)
Historically, water resource management in Indonesia has faced significant complexities, often dominated by commercialization and investment-oriented policies that threaten the fundamental rights of farmers. The Constitutional Court’s decision to annul the previous Water Resources Law marks a crucial turning point, demanding a comprehensive policy reformulation. This entails a shift from a market-based paradigm to one grounded in human rights and social welfare, reaffirming state sovereignty over water for the prosperity of the people. The urgency of this reformulation is compounded by the imminent threat of climate change, which introduces high uncertainty into the hydrological cycle—manifesting as extreme droughts and floods—thereby directly impacting the agricultural sector. This research aims to formulate a climate-adaptive water resource management policy that secures the priority rights of farmers. Employing a Normative Legal Research Method with Statutory and Conceptual Approaches, the findings present a new, holistic legal and institu-tional framework. This framework centers on two pillars: first, the firm assertion and absolute legal protection of irrigation water allocation for farmers, even during periods of scarcity; and second, the adoption of a Climate-Adaptive Governance Model. This governance model integrates a unified climate monitoring system, resilient water infrastructure, and the empowerment of Water User Associations (P3A) at the grassroots level to independently respond to shifting climate patterns. This reformulation is essential for achieving water management that is just, sustainable, and effective in maintaining national food security